Examining Debate in Developing Higher-order Thinking Skills: A Case of English Language Class in Senior High School Context - Susianti Rosalina; Hanna Sundari (INFERENCE: Journal of English Language Teaching, 2022)
The concept of higher-order thinking skills (HOTS) has become an important issue in 21st-century learning. One of the skills reflecting higher-order thinking skills is critical thinking that also becomes another important concept that has recently been studied in some researches. The number of previous studies supporting the influence of debate as a beneficial pedagogy on the development of critical thinking skills have been conducted through some researches. However, the studies contradicting the issue also need to be concerned to consider the influence of debate particularly in enhancing critical thinking in English language class. Having conducted a study by using a quantitative method and objective assessment, the purpose of the present study was to find significant effect of debate on the development of students’ higher-order thinking skills in English language class. The study was conducted in public senior high school 1 in Bogor, West Java, Indonesia, involving 68 students divided into two groups. The result shows that there was no significant mean difference of the scores obtained, despite the higher scores achieved by the experimental group in which the group using debate, since the th is lower than the tt(1.21 < 1.669). In other words, the study reveals that debate does not have significant effect on the development of higher-order thinking skills. Some possible reasons are then discussed and illustrated.